ANALISIS STRATEGI PENINGKATAN KUALITAS RUANG TERBUKA HIJAU (RTH) DALAM KERANGKA PEMBANGUNAN BERKELANJUTAN DI KECAMATAN MEDAN BARAT - Cindy Meyanda; Jhonson Pasaribu; Artha Tobing (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The primary objective of this work is to comprehensively analyze public administration strategies in optimizing the quality of Green Open Space (GOS) as a central pillar of the sustainable development framework in Medan Barat District, Medan City. The urgency of this study is rooted in the persistent performance gap phenomenon, where the current GOS coverage remains stagnant at 7-9%, a figure systematically far below the 30% mandatory threshold mandated by national regulations. This discrepancy is driven by irreversible spatial constraints in the urban core resulting from massive commercial land conversion. The approach employed in this study is descriptive qualitative, relying on data collection techniques such as in-depth interviews with key informants, participatory field observations, and documentation studies of local policy reports. The data analysis process was conducted interactively, ranging from data reduction to conclusion drawing, to ensure the validity of the findings. The data presented in the discussion reveals that the Medan Barat District Government has undergone a paradigm shift from high-cost land acquisition policies to an inward-looking strategy focusing on functional asset optimization. This innovation is realized through the adoption of green infrastructure based on Low Impact Development (LID), such as the "Sponge Infrastructure" concept for flood mitigation and the development of "Green Alleys" in high-density residential areas like Glugur Kota and Karang Berombak. Furthermore, a strong manifestation of Collaborative Governance was found through the mobilization of CSR funds from the private sector in the Jalan Putri Hijau business corridor, alongside Public-Social Co-production practices involving active local community participation. Regulatory enforcement through the Building Construction Permit (PBG) instrument also serves as a crucial tool in forcing the internalization of negative externalities from commercial building developments. This analysis ultimately concludes that the integration of adaptive management, micro-scale ecological decentralization, and regulatory legal certainty represents the most rational administrative solution to achieve urban resilience, thermal comfort, and distributive justice in environmental services for the entire community of Medan Barat District to ensure intergenerational sustainability.